2017
DOI: 10.1002/adma.201605021
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Peptide‐ and Protein‐Based Nanomaterials for Antitumor Photodynamic and Photothermal Therapy

Abstract: Tremendous interest in self-assembly of peptides and proteins towards functional nanomaterials has been inspired by naturally evolving self-assembly in biological construction of multiple and sophisticated protein architectures in organisms. Self-assembled peptide and protein nanoarchitectures are excellent promising candidates for facilitating biomedical applications due to their advantages of structural, mechanical, and functional diversity and high biocompability and biodegradability. Here, this review focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
373
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 628 publications
(391 citation statements)
references
References 129 publications
1
373
0
Order By: Relevance
“…Beyond structure–stability–activity relationship studies, the incorporation of non‐coded amino acids has been exploited in supramolecular chemistry to modulate the conformational propensities of self‐assembling peptides. It has also been used to introduce spectroscopic probes and photosensitizers for diagnostic and therapeutic applications into self‐assembled synthetic peptides (eg, RGD‐based), polypeptides (eg, poly‐Lys/poly‐Leu) and natural proteins (eg, apoferritin) . In particular, the possibility of being able to conjugate photosensitizer moieties (eg, phthalocyanine, protoporphirin, and purpurin) to self‐assembled peptides/proteins, which are able to locally release heat or cytotoxic reactive oxygen species upon controlled light stimulation, has opened new and promising avenues for the fabrication of biocompatible nanostructures for use in antitumor photothermal and photodynamic therapy …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond structure–stability–activity relationship studies, the incorporation of non‐coded amino acids has been exploited in supramolecular chemistry to modulate the conformational propensities of self‐assembling peptides. It has also been used to introduce spectroscopic probes and photosensitizers for diagnostic and therapeutic applications into self‐assembled synthetic peptides (eg, RGD‐based), polypeptides (eg, poly‐Lys/poly‐Leu) and natural proteins (eg, apoferritin) . In particular, the possibility of being able to conjugate photosensitizer moieties (eg, phthalocyanine, protoporphirin, and purpurin) to self‐assembled peptides/proteins, which are able to locally release heat or cytotoxic reactive oxygen species upon controlled light stimulation, has opened new and promising avenues for the fabrication of biocompatible nanostructures for use in antitumor photothermal and photodynamic therapy …”
Section: Discussionmentioning
confidence: 99%
“…At variance, the development of more efficient carbonyl activators and enhancement of automated synthesizers performances made experimentally accessible the manipulation of even long polypeptide chains (50‐90 amino acids) on laboratory routine basis, by inserting any non‐coded amino acid at any protein site for producing large amount of the resulting mutated chain, from milligrams to grams, for studying protein folding, stability, and function . Recently, the efficiency and versatility of SPPS has been extensively exploited to introduce special spectroscopic probes and photosensitizers into self‐assembling peptides for in vivo imaging studies or for the construction of biocompatible supramolecular nanostructures to be used in antitumor photodynamic and photothermal therapy . Furthermore, photo‐inducible chromophores (eg, tris‐bipyridyl stable complexes of ruthenium[II]) have been successfully incorporated at the N‐terminus of alanine‐rich peptides to monitor ultrafast kinetics of helix‐coil conformational transition …”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic Nanoagents Based on Peptide-Modulated Self-Assembly of Photosensitizers PDT, compared with traditional cancer treatment methods, is a minimally invasive and effective method that has been approved by the FDA for some clinical treatments. [32] Our group introduced the cationic diphenylalanine (H-Phe-Phe-NH 2 ·HCl, CDP), which was derived from FF, as a model of an amphiphilic dipeptide for use in combination with another amphiphilic amino acid, 9-fluorenylmethoxycarbonyl-l-lysine (Fmoc-l-Lys). [30] De-excitation then immediately occurs by intersystem crossing to form a triplet state.…”
Section: Nanodrugs Based On Peptide-modulated Self-assembly Of Drugsmentioning
confidence: 99%
“…They are classified based on number of amino acid conjugates attached to ferrocenyl group and are termed mono‐, di‐, and tri‐peptides. Among them, the behavior of ferrocene‐phenylalanine–phenylalanine (Fc–FF) has been studied in details . Wang and Qi et al reported that Fc–FF changed the conformation of the secondary structures from the flat β‐sheets conformation of phenylalanine–phenylalanine (FF) into twisted β‐sheets, and the detailed diameters of the twists can be controlled by counterions, temperature, and solvents .…”
Section: Introductionmentioning
confidence: 99%